0189 Simulated complex clinical procedural skills in situ – Bridging the gap between the lab and real clinical practice. (1st November 2014) - Tiernan, James; Millar, Eoghan; O'Connor, Lanty; Humphrey, Vanessa; Edgar, Simon
Abstract : Background: Postgraduate medical curricula contain mandatory procedural skills, including lumbar puncture, thoracocentesis and central venous cannulation. Simulated skills training can improve technical ability in laboratories but does this ensure safe clinical performance? We propose that the environment significantly affects procedural skill performance, and that using simulation in the 'real-life' clinical environment will bring us closer to ensuring safe and successful practice. Methodology: The NHS Lothian Clinical Skills Mastery Programme was introduced in Edinburgh in 2013. For each procedural skill, trainees receive knowledge packs (written and video resources) and a 2-phase supervised simulated training programme. Phase 1: Skills lab (non-clinical) Phase 2: In situ (clinical environment) We are currently studying the development of a complex clinical procedural skill (lumbar puncture) by our trainees via our Mastery methodology, with particular focus on the impact of the environment on performance. This study takes the form of a randomised control trial, using 2 groups of candidates: Lab Simulation 'vs. In Situ Simulation. Both groups undergo a series of formative, standard-set, checklist-based assessments, culminating in an assessment of simulated performance in situ . Results: A combination of quantitative and qualitative data from our study will be presented. Conclusions and recommendations: 'Mastery Learning' has an evidence base to support its methodology in the development of clinical skills in the USA. This study aims to expand the established literature, demonstrating measurable improvement in the simulated performance of a complex clinical procedural skill by UK trainees. The environment can negatively impact on skill performance and we believe that simulation within the clinical environment is the key to improving skill levels in a meaningful way. This dramatically improves fidelity and provides the additional challenge of progressing from motor skill to psychomotor, whereby trainees must employ their newly-acquired non-technical skills to ensure technical success and patient safety. References: McGaghie W, Issenberg SB, Barsuk JH, et al . A critical review of simulation-based mastery learning with translational outcomes. Med Educ 2014;48:375–385 Barsuk JH, Cohen ER, Caprio T, et al . Simulation-based education with mastery learning improves residents' lumbar puncture skills. Neurology 2012;79:132–7 Wayne DB, Barsuk JH, O'Leary K, et al . Mastery learning of thoracentesis skills by internal medicine residents using simulation technology and deliberate practice. J Hosp Med 2008;3:48–54